Djerba: Beitrag zur Kulturgeographie Südtunesiens - Suter, Karl (ERDKUNDE, 1960)
The isle of Djerba in southern Tunisia, only 514 sq. Km. large, belongs to the steppe zone of the southern Mediterranean, and its climate is characterised by hot and dry summers and mild, moderately humid, winters. This climate permits the successful cultivation of olives and dates, and in addition modest grain and vegetable growing is practised. The inhabitants distinguish four types of cultivated plots: menzel (garden with dwelling house), djnan (fruit garden), sania (vegetable garden with well for irrigation) and frawa (olive grove). Except for the latter type it is typical of all these gardens to be surrounded by high hedges. Djerba’s characteristic settlement type is dispersed. The siting of the farmsteads is utterly independent of edaphic features as occurrence of water, altitude, topography and soil types. This independence is possible since the Djerbis depend for their water supply on wells. There is at least one per dwelling house, but in many cases there are two. Borings for suitable freshwater, apart from a single case, have so far had no success. The dwelling house of the island (called dar) consists of a single room which is divided into three sections. The central section serves as living quarters, whereas the adjoining ones on either side are used for sleeping. One of the latter is regularly covered by a dome (quba); this is used during the winter. The other is covered by a cubical structure with windows (ghorfa). This is used for sleeping in summer. In the latter case the sleeping accommodation is raised 3 m. above the ground and the washing facilities are underneath this raised bunk. Two or three houses are normally combined in a single structure (haouch); this is inhabited by related families and has also communally used rooms as kitchen and storage space. Somewhat different from this are the Jewish houses of the two settlements Hara Kbira and Hara Shrira. The total number of inhabitants of the isle is 60,000; they are Berbers, or rather Arabised Berbers. They belong to two different Mohammedan denominations, the Malikis and the Ibadites. There are numerous mosques on the isle. The main occupation is horticulture, additional ones are fishing, pottery and the making of carpets and wall mats. Since these occupations are insufficient to provide an adequate livelihood for the population, many Djerkis emigrate, especially to the towns of Tunisia. There they have a high reputation as traders in cloth and spices. Emigration is, however, only of the temporary type. The principal settlement is the small market town of Houmt-Souk.